Harapan Kemandirian Masyarakat melalui Program Keluarga Harapan (PKH) - Zainab ,; Nur Farida; Muchsin Zuhad Al’asqolaini; Ali Tofan; Enza Resdiana (Abhakte Jurnal Pengabdian Kepada Masyarakat, 2023)
PKH is a social assistance program that provides financial assistance to poor families, with predetermined terms and conditions, especially in the fields of education, health, and social welfare. The purpose of the PKH program itself is to reduce the number and break the chain of poverty, improve the quality of human resources, and change behavior that does not support the improvement of the welfare of the poorest groups. One form of success of the PKH program is that many people do not want to receive assistance from this program because they feel financially capable. The formation of people's mindset on independence needs to be improved and disseminated so that this PKH program is able to reduce poverty in Indonesia.